Emerging Journalistic Verification Practices Concerning Social Media. (2nd April 2016) - Brandtzaeg, Petter Bae; Lüders, Marika; Spangenberg, Jochen; Rath-Wiggins, Linda; Følstad, Asbjørn
Abstract : The verification of social media content and sources are increasingly critical to journalists and news organisations. In this study, we report on findings from qualitative interviews conducted with 24 journalists working with social media in major news organisations in Europe. Our findings contribute to new knowledge on journalists' social media working practices. We find that social media content are often used as the primary news source, and journalists use several different verification strategies to verify social media content and sources. Journalists are also found to have various competences in verifying social media content, in particular visual content. Moreover, our study suggests user requirements for future innovations in tools to support the verification of social media content. To avoid trade-offs between verification and fast-paced publishing, journalists will need efficient and easy-to-use support both in the verification process and in structuring and organising an overwhelming amount of social media content.